Investigating Social Support and Network Relationships in Substance Use Disorder Recovery. Issue 4 (October 2015) - Stevens, Ed; Jason, Leonard A.; Ram, Daphna; Light, John
Background: Social support and characteristics of one's social network have been shown to be beneficial for abstinence and substance use disorder recovery. The current study explores how specific sources of social support relate to general feelings of social support and abstinence-specific self-efficacy. Methods: Data were collected from 31 of 33 individuals residing in 5 recovery houses. Participants were asked to complete social support and social network measures, along with measures assessing abstinence from substance use, abstinence self-efficacy, and involvement in 12-step groups. Results: A significant positive relationship was found between general social support and abstinence-specific self-efficacy. General social support was also significantly associated with the specific social support measures of sense of community and Alcoholics Anonymous (AA) affiliation. Social network size predicted abstinence-related factors such as AA affiliation and perceived stress. Conclusions: These results provide insight regarding individual feelings of social support and abstinence-specific self-efficacy by showing that one's social network-level characteristics are related to one's perceptions of social support. We also found preliminary evidence that individual Oxford Houses influence one's feelings of social support.